Internal factors affecting the performance of workers: A case study in MASkargo Penang / Jamal Mohd Farid Baharuddin and Mohamad Nazril Abd Wahab - Baharuddin, Jamal Mohd Farid; Abd Wahab, Mohamad Nazril (2010)
The objective of this article is to study about the internal that affecting the performance of MasCargo to fulfill their goal, objectives, vision and mission. The result indicates that there were several internal factors affecting the workers performance in MASkargo. First is size of organization, ISO 9001 which related to management, strategic management and Employee Recognition Programs.